Design and CFD analysis of baffles of fuel tanker trucks for normal and grade highway conditions. (14th August 2020) - Ahmad, Nafees; Varshney, Mehul; Farooqi, Mohammad Haani
Liquid sloshing is a kind of wave motion inside a partially filled tank. Fluid sloshing affects the stability of fuel tanker truck, because of the movement of the centre of gravity during different dynamic conditions on normal as well as on the grade highways. Hence, controlling sloshing is of prime importance for the prevention of accidents and casualties. For the present work, the tanker truck filled with kerosene fuel has been considered. The baffles are designed to control the phenomenon of sloshing to a maximum extent. The computational fluid dynamics (CFD) analysis of the tank with and without baffles is performed using Fluent® to study the amplitude of sloshing at different time instants. The baffles are designed in a way to ensure no hindrance during loading and unloading of the tanker truck.